EFFECTIVENESS OF 5E LEARNING CYCLE IN DYNAMIC ELECTRICTY KELAS X SMA NEGERI 3 MEDAN - Carolina Nainggolan; Eidi Sihombing (INPAFI (Inovasi Pembelajaran Fisika), 2013)
ABSTRACT The purpose of this research was to find out the effectiveness of 5E learning cycle in dynamic electricity kelas X SMA Negeri 3 Medan in Academic Year 2012/2013. The research method was quasi experiment. The samples were divided into experiment and control class. Population in this research was all students of grade X in SMA Negeri 3 Medan. The sample in this research consist of two class X1 as experiment class and X2 as control class determine by simple random sampling. The results that were obtained: (1) the post-test mean value of the experiment class was 76.29 is good category and 69.29 was the mean value for control class is good enough category. Standard deviations for both classes were 10.31 and 9.48. The t count was 2.94 and t table was 1.99 then the tcount > ttable. Hence, alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected.(2) Furthermore, the mean value of student’s  learning outcomes in experiment class from affective and psychomotor domain were 72.68 and 71.6 while in control class were 69.7 and 69.8. It was concluded that there were no effect difference of 5E learning cycle and direct instruction learning model for affective and psychomotor domain on students learning outcomes in dynamic electricity.(3) In addition, the mean value of instrument’s sensitivity index in experiment class was 0.320  that was sensitive category while in control was 0.281  which meant that was not sensitive category. The percentage the result of class learning mastery in experiment class was 85.7% that was categorized passed meanwhile in control class was 57.1 % that categorized not passed. Then, the mean value of activities observation result in experiment class was 73.15 while in control class was 68.15 that were included in good category. It was concluded that 5E learning cycle is more effective than direct instruction learning model. Therefore, the effectiveness of 5E learning cycle was high on the student’s learning outcomes   Keywords: 5E learning cycle model, learning outcomes, effectiveness